Effect on The Surface Roughness During Turning of EN-31 Steel At Different Environment - Ajay Kumar, Gurpreet Singh (International Journal of Advanced Science and Technology, 2020)
Surface roughness play an important to achieving desire degree of accuracy in any machining process .to achieve this flood lubrication is used which play very bad effect on the health and also increase the cost. this paper experimentally show that in which manner MQL process is better than the dry or flood lubrication and give more effective results on surface roughness as compare to the other one.